Self-assessment in higher education: students’ perception of its usefulness in the learning process - Ramírez Olivares, María Isabel (2023)
Introduction: Learning assessment is a process where it is important to incorporate students through self-assessment, to involve them and make them responsible for their learning. Objective: To investigate the usefulness of self-assessment from the perspective of higher education students. Method: The methodology is mixed, with a qualitative analysis carried out in ATLAS.ti and a quantitative analysis developed in SPSS and Excel. Results: Self-assessment is not frequently used since only 23% of the participants have used it with a high frequency. Conclusions: a) An area of opportunity is for students to compare their learning with their peers’, b) for effective self-assessment, students must strengthen their confidence in themselves, c) it is necessary for teachers to incorporate activities after self-assessment, d) the use of self-assessment is useful if its implementation has a goal and a structured process.